2015
DOI: 10.6026/97320630011307
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Docking studies of FKBP12-mTOR inhibitors using binding predictions

Abstract: Mammalian target of rapamycin (mTOR) is a key regulator of cell growth, proliferation and angiogenesis. mTOR signaling is frequently hyper activated in a broad spectrum of human cancers thereby making it a potential drug target. The current drugs available have been successful in inhibiting the mTOR signaling, nevertheless, show low oral bioavailability and suboptimal solubility. Considering the narrow therapeutic window of the available inhibitors, through computational approaches, the present study pursues t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 29 publications
0
19
0
1
Order By: Relevance
“…Subsequently, all cavities were detected to get high volume cavity and hence the highest volume cavity (>2000Å) was selected for docking and to target the active of the IDH2 structure (PDB ID: 5SVN) with the pre-prepared 4 ligands. The docking procedure parameters were selected as required, having a maximum population size of 50, maximum iteration of 1,500 and 0.20Å as grid resolution (Khandelwal et al, 2018;Bandaru, 2017b;Majhi et al, 2018;Nasr et al, 2015). Further, the post-docking process carries hydrogen bonds optimization and energy minimization, Simplex Evolution at max steps 300 and neighbor distance technical setting fast at 1.00 (Sharda S et al, 2019;Ali MA et al, 2019).…”
Section: Molecular Dockingmentioning
confidence: 99%
“…Subsequently, all cavities were detected to get high volume cavity and hence the highest volume cavity (>2000Å) was selected for docking and to target the active of the IDH2 structure (PDB ID: 5SVN) with the pre-prepared 4 ligands. The docking procedure parameters were selected as required, having a maximum population size of 50, maximum iteration of 1,500 and 0.20Å as grid resolution (Khandelwal et al, 2018;Bandaru, 2017b;Majhi et al, 2018;Nasr et al, 2015). Further, the post-docking process carries hydrogen bonds optimization and energy minimization, Simplex Evolution at max steps 300 and neighbor distance technical setting fast at 1.00 (Sharda S et al, 2019;Ali MA et al, 2019).…”
Section: Molecular Dockingmentioning
confidence: 99%
“…Targeted three-dimensional structural coordinates was pre-processed using Protein Preparation Wizard module in Schrödinger Suite (Protein preparation wizard, Schrodinger, 2017) (Sharda et al, 2017;Bandaru et al, 2017) by implying the parameters like assigning bond orders, zero-order bonds to metal atoms, selenomethionine to methionine conversion, filling absent hydrogen's, capping termini, side chains and loops, and removing waters beyond 5 Å distance surrounding the co-crystallized ligand (Bandaru et al, 2017;Shameer et al, 2017;Nasr et al, 2015;Khandekar et al, 2016;Singh et al, 2019). Further, tautomerization and protonation states were predicted in favor of ligand at pH 7.00.…”
Section: Preparation Of Proteinmentioning
confidence: 99%
“…Though the analogues have achieved some clinical success, however, it still has some side effects: mainly in the lower stability, poorer bioavailability and lower water solubility [12] . The latest study found that some small molecule inhibitors of mTOR kinase could inhibit both mTORC 1 and mTORC 2 , such as PP242, a kind of selection mTORC 1 /C 2 inhibitor, can block the Akt kinase by phosphorylating at Ser473 [13][14][15] . Perhaps, the dual inhibitors of mTOR kinase and PI3K are the most effective antitumor inhibitors.…”
Section: Research Papermentioning
confidence: 99%